Negative Reinforcement, Obsessive-Compulsive Disorder (OCD), and Exposure and Response Prevention (ERP) Strategies: A Narrative Review of Literature - Carneiro, Juliana Margarida; Bertelli, Rosangela (Advances in Social Sciences Research Journal, 2022)
Clinical evidence has increasingly shown that Obsessive-Compulsive Disorder (OCD) can be effectively treated through psychotherapeutic interventions. Considering that there currently is a high diversity of psychotherapeutic interventions, how can health professionals decide on which strategies to use? What are the characteristics of the strategies effectively applied to treat OCD? The aim of the present review of clinical reports was to provide an overview of strategies employed in the psychotherapeutic treatment of OCD. The bibliographic research carried out through the Online Library of Knowledge (B-on) allowed for the identification of 23 publications that met the inclusion criteria for the present narrative review of the literature. Results revealed that amongst several strategies derived from the cognitive-behavioural model of learning, Exposure and Response Prevention (ERP) strategies applied in order to extinguish behaviours shaped by negative reinforcement directed many health professionals' attention.